A CASE SERIES OF ACUTE POSTOPERATIVE ENDOPHTHALMITIS: MANAGEMENT AND OUTCOMES (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Background: Endophthalmitis is one of the rare and most devastating complications of intraocular surgery. Although the prevalence of post-cataract surgery endophthalmitis is very small, it has become an important eye health problem. Case Presentation: Six patients, 5 male and 1 female, were diagnosed with post-phacoemulsification endophthalmitis on the same day. Four patients had a visual acuity of 1/300, and two patients had 6/60. All patients underwent intravitreal injection of vancomycin-ceftazidime, and culture samples were taken from the vitreous tap and AC tap. Five patients were planned to undergo pars plana vitrectomy. Intravitreal injection of triamcinolone acetonite was performed on 1 patient, due to macular oedem. Brevundimonas diminuta was found from 1 patient and Stenotrophomonas maltophilia from 1 patient. Final visual acuity in 4 patients was bigger than 6/30, and 3/60 in 1 patient. Discussion: Management must be carried out immediately, once there is a suspicion of acute postoperative endophthalmitis. All patients had intravitreous injection of vancomycin-ceftazidime. Pars plana vitrectomy was performed on 5 patients with 80% having final visual acuity bigger than 6/30. Intravitreal injection of antibiotics followed by pars plana vitrectomy can provide a good prognosis for final visual acuity, although various factors predispose to poorer prognosis. Conclusion: Intravitreal injection of antibiotics and pars plana vitrectomy is a treatment for acute postoperative endophthalmitis, where this action will provide a good prognosis for the patient's final visual acuity if done immediately..